2012
DOI: 10.1007/s11422-011-9371-1
|View full text |Cite
|
Sign up to set email alerts
|

The importance of place in indigenous science education

Abstract: In this issue of Cultural Studies of Science Education, Mack and colleagues (Mack et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…The current research found that this construct was very important as revealed in themes regarding the skills needed to create a resource and in understanding open publishing. These findings are consistent with OER research conducted outside of the UTAUT framework (Butcher, 2015;Towey et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current research found that this construct was very important as revealed in themes regarding the skills needed to create a resource and in understanding open publishing. These findings are consistent with OER research conducted outside of the UTAUT framework (Butcher, 2015;Towey et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Much research has explored the positive impact on student learning when OER are freely offered (Colvard et al, 2018;Lieberman, 2018). Other research has indicated the importance of place in culturally relevant science education (Sutherland & Swayze, 2012). Instructors in this research were particularly excited about the localization of the content and felt that it positively impacted their teaching experience with the students, which is consistent with outside research (Ivins, 2011).…”
Section: Discussionsupporting
confidence: 76%
“…IK is inherently interdisciplinary, multigenerational, and expressed through sustainable practices 3 . Additionally, connection to place has been identified by numerous researchers, including traditional knowledge holders, as an essential component in indigenous education 4,5 .…”
Section: Aparna Venkatesan David Begay Adam J Burgasser Isabel Hamentioning
confidence: 99%
“…Environmental learning education often involved nature study and the development of an understanding and appreciation of natural environment through experiential learning (Sutherland & Swayze, 2012). Environmental learning associated with place integrates humans and nature and develops ecosystems knowledge characteristic of sustainable cultures (Chinn, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%